Experimental Study of Stabilized Soil Utilizing Circulating Fluidized Bed Combustion Desulfurization Ash with Carbide Slag and Desulfurization Gypsum - Dezhi Shao; Jinlong Liu; Xin Huang (Journal of Engineering)
This paper discusses the feasibility of preparing soil stabilizer which is circulating fluidized bed combustion ash-based, supplemented with carbide slag and desulfurization gypsum, composed entirely of complete industrial wastes. The results show that CFBC ash has better pozzolanic activity than fly ash. When stabilizer total content is 10% and the ratio of CFBC ash : carbide slag : desulfurization gypsum is 7.2 : 1.8 : 1, compressive strength of stabilized soil can reach the maximum of 2.12 MPa at the age of 28 d of curing. Stabilizer can meet the strength requirements of cement-soil mixing pile composite foundation and cement-soil mixing pile waterproof curtain.